2018
DOI: 10.1007/s12031-018-1167-2
|View full text |Cite
|
Sign up to set email alerts
|

A Novel SYNJ1 Mutation in a Tunisian Family with Juvenile Parkinson’s Disease Associated with Epilepsy

Abstract: Mutations in SYNJ1 gene have been described in few families with juvenile atypical Parkinson disease (PD). This gene encodes for "Synaptojanin 1," an enzyme playing a major role in the phosphorylation and the recycling of synaptic vesicles. In this study, we report two siblings, from a consanguineous Tunisian family, presenting juvenile PD. Both siblings developed mild Parkinsonism at 16 and 21 years old respectively. One patient had generalized tonic-clonic seizures since the age of 7 years. There was no evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…MAGMA analyses also identified SYNJ1 as significant in this association. Mutations in SYNJ1 are linked to Parkinson’s disease, but its association with platelet reactivity has not been previously described 41,42 . Regression models adjusted for CYP2C19*2 also demonstrated a suggestive association with SYNJ1 , and for NR3C2 , known to be associated with schizophrenia 37 …”
Section: Discussionmentioning
confidence: 95%
“…MAGMA analyses also identified SYNJ1 as significant in this association. Mutations in SYNJ1 are linked to Parkinson’s disease, but its association with platelet reactivity has not been previously described 41,42 . Regression models adjusted for CYP2C19*2 also demonstrated a suggestive association with SYNJ1 , and for NR3C2 , known to be associated with schizophrenia 37 …”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, GWAS studies have identified genetic variations and altered expression of GAK, the ubiquitously expressed version of neuronal-specific auxilin, among the top risk factors for familial PD across multiple populations worldwide (Pankratz et al, 2009;Tseng et al, 2013;Nagle et al, 2016). Several mutations in synaptojanin-1 have also been linked to early onset Parkinsonism (Krebs et al, 2013;Chen et al, 2015;Ben Romdhan et al, 2018). Transgenic mice carrying one of the synaptojanin-1 mutations (R258Q) in the Sac domain accumulated CCVs within their synapses and exhibited impaired synaptic vesicle recycling, as well as motor deficits and increased death (Cao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GWAS studies have identified genetic variations and increased expression of GAK, the ubiquitously expressed Hsc70 co-chaperone, amongst the top risk factors for familial PD across multiple populations worldwide (Pankratz et al, 2009;Tseng et al, 2013;Nagle et al, 2016). Several mutations in synaptojanin 1 have also been linked to early onset Parkinsonism (Krebs et al, 2013;Chen et al, 2015;Ben Romdhan et al, 2018). Transgenic mice carrying one of the synaptojanin I mutations (R258Q) in the Sac domain accumulated CCVs within their synapses and exhibited impaired synaptic vesicle recycling, as well as motor deficits and increased death (Cao et al, 2017).…”
Section: Discussionmentioning
confidence: 99%